Analysis of Marketing Mix Relationships on Patient Satisfaction and Loyalty in the Laboratory Unit of X Hospital in 2022 - Fadhilah, Wasiyah Khusna; Katmini, Katmini (Asian Journal of Health and Applied Sciences, 2023)
A healthcare facility, one of which is a hospital, must practice management more quickly as the environment changes due to global competition. In order to sustain client loyalty and satisfaction, X Hospital must maintain and enhance its services. Companies must devise the best marketing strategy to deal with the challenge of the Service Marketing Mix's influence on consumer purchase decisions. Especially for service marketing (7p) in the form of products, prices, promotions, places, people, processes and physical evidence. The hospital has important medical support, one of which is a laboratory. The laboratory unit has not conducted a service satisfaction survey. Conducting a service survey is crucial as a critical component of medical diagnosis. This is also based on the 2019 X Hospital's first-semester periodic report, 49.95% of patients received laboratory services. This amount fell short of the predetermined goal. Further investigation is required to determine how patient loyalty and satisfaction in the laboratory unit of X Hospital might be impacted by the analysis of marketing mix relationships. This research aims to analyse the relationship between the marketing mix and patient satisfaction and loyalty in the laboratory unit of X Hospital in 2022. The method employed is analytic quantitative with a cross-sectional approach. The result of the direct influence value is 0.077 and the indirect effect is 0.556, meaning that the indirect effect value is greater than the direct influence value. The research's conclusion there is a relationship between the marketing mix and customer satisfaction and loyalty at X Hospital's laboratory unit in 2022.